Engineering geometrically bi-linear columns to deliver fire resistance: Standard heating. (1st October 2015) - Law, Angus; Kotsovinos, Panagiotis; Butterworth, Neal
Highlights: A composite steel structure was designed in accordance with current design guidance. Where columns were geometrically bi-linear, these frequently did not achieve the specified fire resistance. An analytical formulation was developed to predict the failure temperature. It was found that by applying the analytical formulation fire resistance could be significantly improved. Abstract: This paper demonstrates the need for structural fire engineering in the design and specification of unusual structural arrangements. It is found that the required fire resistance of a structure cannot necessarily be achieved by considering only the fire resistance of individual elements of structure. A case study of columns that have a change of direction over their height (geometrically bi-linear columns) is used to illustrate how unusual arrangements may lead to early failure of key structural elements – even where design guidance is followed. These arrangements are parameterised to allow the relative importance of a number of key variables to be studied. A methodology is developed to estimate the required limiting temperature for the governing elements of the assembly in order to deliver the required performance.